Pengembangan Video Penelitian Kuantitatif dalam Meningkatkan Kemampuan Analisis Data Mahasiswa - Af’idah, Irma Nur; Afrida, Fira Nadliratul; Nuraini, Latifah (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
This research aims to develop video tutorials on quantitative methods in correlation and regression analysis. This type of research is Research and Development (R&D) with the ADDIE approach, namely Analysis, Design, Development, Implementation and Evaluation. The results obtained in this research were that the design stage included material and appearance, the development stage was a continuation of the design stage, the implementation stage was carried out on 60 semester 5 students. Next, evaluate the results of the video tutorial based on suggestions and comments from media expert validators and material experts. The average feasibility test results obtained were 85.625% in the very feasible category. The resulting learning video is considered very feasible and effective in improving students' data analysis skills with an improvement score of 29, 47%.